Pengaruh Jumlah Uang Beredar, Investasi Domestik dan Tenaga Kerja Terhadap Kinerja Perekonomian Indonesia - Lorenza Ayu Ningsih; Syamsul Amar (Jurnal Kajian Ekonomi dan Pembangunan, 2020)
This study aims to determine the effect of the money supply, domestic investment and labor on the performance of the Indonesia economy with secondary data in the form of time series from 1987 to 2018 and multiple regression analysis (OLS)  techniques are used which show that partially the money supply had a negative and not significant effect on the performance of the Indonesia economy with a probability of 0.5226 >α =5%; domestic investment and labor had a positive and significant effect on economic performance Indonesia with a probability of 0.0000 < α = 5%; the money supply, domestic investment and labor together have a positive and significant effect with F-Statistic probability of 0.0000 <α = 5% on the performance of the Indonesia economy. Appropriate controls are needed from Bank Indonesia to avoid excessive money supply  and the goverment must implement other policy measures that will encourage the performance of the Indonesia economy wih a comprehensive understanding of the development of domestic investment and Indonesia labor.